Gender Questions at the Margins: The Case of Nomadic and DNT Communities. Issue 2 (December 2018) - Agrawal, Anuja
The nomadic and denotified (DNT) communities are one of the extremely marginalized segments of Indian society. Although they are internally differentiated, they have some significant common concerns that are not necessarily identical with those plaguing other marginal groups. This article provides a broad overview of gender issues which are particularly critical for these communities but which have barely received any systematic attention. Drawing upon the author's research and interaction with members of these communities as well as government reports and other secondary sources, the article examines these issues from the point of view of the marginal position of these groups vis-à-vis the larger society as well as from the perspective of institutions and practices prevalent within these groups. The author argues that gender issues should be integral to policy frameworks as well as other debates about nomadic and DNT communities.